2019
DOI: 10.1080/2162402x.2019.1655360
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal glioblastomas are characterized by an increased immune cell presence compared to Proneural and Classical tumors

Abstract: Glioblastoma (GBM) is the most aggressive malignant primary brain tumor in adults, with a median survival of 14.6 months. Recent efforts have focused on identifying clinically relevant subgroups to improve our understanding of pathogenetic mechanisms and patient stratification. Concurrently, the role of immune cells in the tumor microenvironment has received increasing attention, especially T cells and tumor-associated macrophages (TAM). The latter are a mixed population of activated brain-resident microglia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
87
3
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 73 publications
9
87
3
3
Order By: Relevance
“…Notably, the expression of PN or MES markers did not allow us to distinguish between these two immune subtypes of GBMs. These results differ from some computational [7] and IHC [9,10] studies, showing the enrichment of myeloid and lymphoid cells in the MES subtype. Another study, however, observed an accumulation of CL tumors among GBMs with a high immune in ltrate [8].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Notably, the expression of PN or MES markers did not allow us to distinguish between these two immune subtypes of GBMs. These results differ from some computational [7] and IHC [9,10] studies, showing the enrichment of myeloid and lymphoid cells in the MES subtype. Another study, however, observed an accumulation of CL tumors among GBMs with a high immune in ltrate [8].…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, gliomas are far from being a homogenous entity and disparities in their immune content might also condition their response to different therapeutic strategies. In order to classify the immunological pro le of glial tumors, several groups have used computational and immunohistochemical (IHC) analysis approaches [7][8][9][10]. Here, we have performed a comprehensive characterization of the tumors by ow cytometry.…”
Section: Introductionmentioning
confidence: 99%
“…They also displayed significantly higher expression of immune checkpoints such as PDL1 , in line with Liu et al (2017), and CTLA4, indicating they could be good candidates for immune checkpoint inhibitors therapies. Although others have previously reported similar finding in mesenchymal tumors (Chen and Hambardzumyan, 2018; Doucette et al , 2013; Kaffes et al , 2019), we provide here an alternative strategy based on unsupervised learning, without making any prior assumption on the tumor molecular subtypes. Our approach enables to identify tumors from other molecular subtypes presenting a similar immune and stromal phenotype, which could also benefit from treatments targeting the microenvironment.…”
Section: Discussionmentioning
confidence: 87%
“…Similar expression patterns were also reported for other immune checkpoints such as PD-L1 [29], B7-H3 [26], TIM-3 [27], CD155 [30], and PTPN2 [28] in glioma. Besides, Kaffes et al found highest immune cells presence in mesenchymal GBM compared with other subtypes [31]. These results suggested mesenchymalsubtype gliomas may be more amenable to immunotherapy.…”
Section: Discussionmentioning
confidence: 95%